Women and Islamisation: Contemporary Dimensions of Discourse on Gender Relations Edited by Karin Ask and Marit Tjomsland, Berg, Oxford, 1998,1999 pp. (American Journal of Islam and Society, 1999)
The book is an edited collection of papers, the majority of which were presentedat a conference organized in 1994 by the Chr Michelsen Institute inBergen, Norway, under the title Construction of Gender Relations in Processesof Modernisation: Women and Islamisation. It is divided into seven chaptersand an introduction. Generally, the book attempts to comprehend so-called“religious fundamentalism”; specifically, it examines Islamic fundamentalism.It endeavors to “analyze the ways in which Muslim women develop distinctvoices and participate in Islamization processes,” thus setting new agendas andredefining their role in society. Since the majority of the researchers are “outsiders”(outside Islam), the editors emphasize two points that are of crucialimportance for the credibility of the work. First, unlike most Western studieson gender and Islam, this one claims to be conducted with sincere and goodintentions, with an effort to distance itself from Western prejudices that sooften portray Muslim “women’s relation to Islam as being universally its victims.”Second, this study considers cultural backgrounds, education, class, andage to consideration and assess Muslim women in their various national settings- once again in contrast to the usual Western studies that tend to lumpMuslim women together into one category. Hence the ethnographic cases presentedin the book represent a broad spectnun of Muslim women’s religiousactivities, ranging from Senegal in the West to Iran in the East. The differentcase studies center on Muslim women’s engagement in public religious activities,because it is this involvement which is expected to forge their new roleaway from the fixed traditional patriarchal one. However, their role in the discourseof Islamization does not necessarily address the overall issue of genderrelations; rather, it offers a new alternative and questions the supremacy ofWestern feminism as the ultimate answer to gender equality.In chapter one, titled “Feminist Reinterpretation of Islamic Sources: MuslimFeminist Theology in the Light of the Christian Tradition of FeministThought,” Roald discusses the development of the so-called “Muslim feministtradition,” particularly the attempts by some Muslim women to re-interpret theIslamic sources from a female perspective. She focuses on the intellectual ...